PENGARUH KEMAMPUAN, KOMPENSASI DAN MOTIVASI TERHADAP PRESTASI KERJA KARYAWAN PT. PLN (PERSERO) AREA MAGELANG DI KOTA MAGELANG - Hanityo Arif Sanjaya, 09.05.51.0107 (Students Journal of Economic and Management, 2014)
This research is the ability to analyze the effect of ability, compensation and motivation on employee performance PT PLN (Persero) in Magelang area the city of Magelang. The samples used in this study were 51 respondents. And sampling was done by using saturated samples. For the analysis using validity, reliability test, t test, multiple regression analysis and coefficient of determination. The results showed that ability, compensation and motivation are significant positive influence on employee performance. Of the three independent variables motivational variables have the greatest influence on employee performance. Keywords: Ability, Compensation and Motivation on Employee Job Performance